2020
DOI: 10.1021/acs.est.0c03243
|View full text |Cite
|
Sign up to set email alerts
|

On-Site Treatment of Shale Gas Flowback and Produced Water in Sichuan Basin by Fertilizer Drawn Forward Osmosis for Irrigation

Abstract: Fertilizer drawn forward osmosis (FDFO) was proposed to extract fresh water from flowback and produced water (FPW) from shale gas extraction for irrigation, with fertilizer types and membrane orientations assessed. The draw solution (DS) with NH 4 H 2 PO 4 displayed the best performance, while the DS with (NH 4 ) 2 HPO 4 resulted in the most severe membrane fouling. The DS with KCl and KNO 3 led to substantial reverse solute fluxes. The FDFO operation where the active layer of the membrane was facing the feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…185−188 In China, a recent study showed that FPW treated by onsite fertilizer drawn forward through osmosis can promote plant growth, suggesting that the use of treated FPW (<350 mg/L TDS) is promising for irrigation. 185 However, concurrent studies from the U.S. show that uncertainties remain about the adequate treatment of FPW for agricultural use, given findings that mechanisms causing negative impacts on plants can be more synergistic. 186,187 These synergistic effects could be related to combined effects from constitutes, such as boron, organic chemicals, and salt, 186 and the accumulation of contaminants in the suspended solids in FPW, which also function as delivery vehicles to animals and plants.…”
Section: Unconventional Hydrocarbon Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…185−188 In China, a recent study showed that FPW treated by onsite fertilizer drawn forward through osmosis can promote plant growth, suggesting that the use of treated FPW (<350 mg/L TDS) is promising for irrigation. 185 However, concurrent studies from the U.S. show that uncertainties remain about the adequate treatment of FPW for agricultural use, given findings that mechanisms causing negative impacts on plants can be more synergistic. 186,187 These synergistic effects could be related to combined effects from constitutes, such as boron, organic chemicals, and salt, 186 and the accumulation of contaminants in the suspended solids in FPW, which also function as delivery vehicles to animals and plants.…”
Section: Unconventional Hydrocarbon Developmentmentioning
confidence: 99%
“…FPW is primarily reused to make up new fracturing fluid for ongoing HF operations in the field. In addition, FPW has also been reused for road deicing; however, this may cause adverse impacts on the environmental and human health. , Research has also been conducted on the repurposing of FPW for irrigation, livestock and land restoration activities, treating acid mine drainage, and extracting valuable metals to mitigate freshwater withdrawal and maximize resource recovery. In China, a recent study showed that FPW treated by onsite fertilizer drawn forward through osmosis can promote plant growth, suggesting that the use of treated FPW (<350 mg/L TDS) is promising for irrigation . However, concurrent studies from the U.S. show that uncertainties remain about the adequate treatment of FPW for agricultural use, given findings that mechanisms causing negative impacts on plants can be more synergistic. , These synergistic effects could be related to combined effects from constitutes, such as boron, organic chemicals, and salt, and the accumulation of contaminants in the suspended solids in FPW, which also function as delivery vehicles to animals and plants .…”
Section: Fpw Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of produced water would also be required when it is reused (rather than disposed of), for instance, in agricultural irrigation . As an example, a study proposed fertilizer-drawn direct osmosis as a method to recycle produced water . While different applications require different water qualities, produced water recycle typically requires desalination …”
Section: Introductionmentioning
confidence: 99%
“…As reported in literature, the average water consumption in the gas field is 23,400–27,950 m 3 per well, and 15%–80% of the injected fracturing fluid is recovered as flowback water at the wellhead (Iddphonce et al, 2020; Shi et al, 2020). Metal ions, microorganisms, and chemicals constitute the main components of shale gas extraction wastewater (Sun et al, 2019), and it also has the characteristics of high oil (Lester et al, 2015), high salt, and high dissolved organic matter (DOM) (Alessi et al, 2017), which poses a great challenge to the treatment and reuse of shale gas extraction wastewater (Chang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%